Akuntansi Konservatisme Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Agustina Agustina; Rice Rice; Stephen Stephen (Jurnal Dinamika Akuntansi dan Bisnis, 2016)
This study examine the influence of firm size, firm risk, capital intensity, leverage, tax, litigation, ownership structure, and growth opportunity for accounting conservatism.The study population was 129 manufacturing companies listed in Indonesian Stock Exchange between 2009 and 2011. Based on purposive sampling method, 38 manufaturing companies was selected (or 114 observations). Data was selected from the companies’ financial reports and analysed by using multiple linear regression. This study uncovered that. the firm size, firm risk, capital intensity, leverage, tax, litigation, ownership structure, and growth opportunity have influence for accounting conservatism collectively. But, only firm size, firm risk, capital intensity, ownership structure and growth opportunity affect accounting conservatism individually in the studied companies.